Fe content effects on structural, electrical and magnetic properties of Fe-doped ITO polycrystalline powders - Aragón F.F.H. (2021)
Fe-doped indium tin oxide (ITO) is an exciting material because it combines the host matrix's good electrical conductivity with the magnetic properties coming from the most earth-abundant transition metal, Fe. In this regard, a single-pot synthesis route based on a polymeric precursor method has been used to produce high-quality undoped and iron-doped ITO with iron content up to 13.0 mol%. The crystal formation in the bixbyite-type structure of all samples is confirmed by X-ray diffraction data analysis. A monotonous decrease of the lattice parameters with the increase of the Fe content is determined, which is consistent with of Fe ions with an oxidation state of 3+ in agreement with the ionic radii difference between In3+ and Fe3+. Raman spectroscopy confirms the bixbyite structure formation and provides evidence of a high surface disorder. 119Sn Mössbauer spectroscopy reveals the formation of only Sn4+ ions. Meanwhile, 57Co Mössbauer spectroscopy suggests the presence of Fe3+ ions in a paramagnetic state. DC magnetization characterization of the Fe-doped ITO nanoparticles confirms the compound's paramagnetic character. The sheet resistance (R/?) measurements provide a lower value for the undoped ITO sample (~0.26 ?/sq) than the one of commercial bulk material. It has been determined that the sheet resistance increases with the Fe content, suggesting the decrease of the conduction electrons density as the iron content is increased. © 2021 Elsevier B.V.